Pipeline Corrosion in CO2 Environment with the Presence of High Amount Organic Acid - Ismail, Mohamad Izzuddin (Universiti Teknologi PETRONAS, 2013)
The threat to the integrity of pipeline is not only from CO2 corrosion but also due to the presence of organic acid which originates from reservoir and injection of acid during Enhanced Oil Recovery (EOR). Corrosion on pipelines is identified as the most common problem caused by the presence of acetic acid (HAc). However, the extent of corrosion problem due to the presence of high amount of HAc is not clear and not really documented. The objective of the project is to study the mechanism of CO2 corrosion in presence of high amount of acetic acid and also determine the effects of CO2 corrosion and high amount of organic acid on the integrity of pipelines. The role of high concentration of acetic acid on a carbon steel pipelines in CO2 corrosion is investigated using Linear Polarization Resistance (LPR) techniques. A series of experiments are conducted to investigate the effect of various concentration of acetic acid on mild steel. A typical brines from North Sea oilfield is synthesized in laboratory to stimulate the field conditions. The oil field production parameters used in this project are typical of a North Sea oil field due to the presence of high concentration of acetic acid found in produced water. A brine similar to the composition of produced water is synthesized in laboratory to stimulate an oilfield brine. All experiments are conducted at fixed temperature, pressure and partial pressure. At the end of the experiments, the corrosion rate of each sample will be calculated using a series of equations. It was observed that general corrosion rate for all concentrations of acetic acid increased slightly with time and then decreased to a stable value. The corrosion rate also increased as the temperature increased. As a conclusion, the presence of dissociated for acetic acid is volatile and can significantly increase the corrosion rate on the mild steel.